The Role of Marxist Ideology Theory in the Construction of Students' Sports Psychology - Mengzhe Ji; Hairuo Bai, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study aims to investigate the impact of Marxist ideological theory on the development of students' sports psychology. This study introduces intermediary variables such as self-efficacy, subjective well-being, and subjective exercise experience, constructs and verifies the research on the psychological mechanism of physical exercise promoting college students' mental health under the influence of Marxist ideology theory, using literature research, data, and other methods. The correlation coefficient ranged between -0.755 and -0.153 between mental health and physical activity, subjective exercise experience, general self-efficacy, and subjective well-being. Practically, the student's performance is crucial. Still, their mental health can boost their learning if their parents urge them to adopt a regimen of physical activity to promote their mental health. Students and their parents can work together to improve the mental health of students, according to the findings of the study. Research in the literature has addressed students' sports psychology, but these earlier studies did not incorporate Marxist theory and ideology. This original study explains the impact of Marxist ideological theory on the sports psychology of students.